Construction and validation of the Life Skills Scale of Physical Education for adolescents. - Pan, Yi-Hsiang; Huang, Chen-Hui; Chang, Yi-Ya; Lee, Chor-Kiu; Hsu, Wei-Ting (International Journal of Sport & Exercise Psychology, 2026)
Developing life skills during adolescence is crucial to social and emotional learning in school. Physical education offers ample opportunities for students to cultivate essential life skills. However, there is relatively limited research on the development of life skill assessment tools for physical education. The purpose of this study was to develop the Life Skills Scale of Physical Education (LSSPE) targeting Taiwanese adolescents. Four studies were conducted to develop LSSPE. Study 1 developed a preliminary LSSPE, including a literature review and 16 expert advisors to ensure content validity. Study 2 included 251 adolescents and employed item analysis, exploratory factor analysis (EFA), and internal consistency reliability analysis to conduct a preliminary analysis of the reliability and validity of the LSSPE. Study 3 examined the scale's validity with a sample of 437 adolescents, using confirmatory factor analysis (CFA) and criterion-related validity analysis. Study 4 examined the test-retest reliability with a sample of 55 adolescents. Study 1 developed a 63-item preliminary scale with content validity. Study 2 used EFA to construct the LSSPE including 7 factors with 34 items. Study 3 refined the LSSPE by CFA, resulting in 7 factors with a 28-item scale. Study 4 demonstrated acceptable test-retest reliability for LSSPE. These studies demonstrated acceptable validity and reliability for LSSPE. It consisted of 7 subscales, including teamwork, goal management, time management, emotional skills, interpersonal interaction, problem-solving and decision-making, and self-reflection, with 28 items. This scale can assess students' development of life skills in physical education.